Acantholytic dyskeratotic acanthoma: case report and review of the literature - Alina Goldenberg (Mattioli1885, 2014)
Background: Focal acantholytic dyskeratosis has been described as an incidental finding and as a clinically distinct lesion. In both situations, a dimorphic histologic pattern is observed: acantholysis and dyskeratosis. Solitary, non-genital lesions displaying such pathology have been difficult to classify. Clinical and pathological characteristics of acantholytic dyskeratotic acanthomas are described.